2022
DOI: 10.1097/ijg.0000000000002158
|View full text |Cite
|
Sign up to set email alerts
|

Early Lensectomy in Patients With Pseudoexfoliation: Long-Term Effectiveness and Safety Outcomes

Abstract: Précis: Early lensectomy in patients presenting pseudoexfoliation (PXF) in an asymmetric clinical stage resulted in effective, safe, and predictable long-term results. Good intraocular pressure (IOP) was found, thus it might be considered as a possible surgical approach in these patients. Purpose:The purpose of this study is to assess the long-term effectiveness, predictability, and safety of cataract surgery performed in patients with capsular PXF at an early stage of the disease. Materials and Methods:This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The study concluded that CML is not a predictive factor for cataract surgery results [ 29 ]. Our analysis therefore included six articles ( Table 2 ) [ 19 , 22 , 23 , 24 , 25 , 26 ]. There were two case-control studies [ 24 , 26 ] and four cohort studies [ 19 , 22 , 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study concluded that CML is not a predictive factor for cataract surgery results [ 29 ]. Our analysis therefore included six articles ( Table 2 ) [ 19 , 22 , 23 , 24 , 25 , 26 ]. There were two case-control studies [ 24 , 26 ] and four cohort studies [ 19 , 22 , 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis therefore included six articles ( Table 2 ) [ 19 , 22 , 23 , 24 , 25 , 26 ]. There were two case-control studies [ 24 , 26 ] and four cohort studies [ 19 , 22 , 23 , 25 ]. Two studies were conducted in Europe [ 22 , 26 ] and four were conducted in Asia [ 19 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations